Multidimensional scale of attitudes toward lesbians and gay men: Construction and preliminary validation | Escala Multidimensional de atitudes face a lésbicas e a gays: Construção e validação preliminar - Jorge Gato (2012)
Prejudice against non-heterosexual individuals persists and currently assumes various forms. This study describes the process of developing and validating a multidimensional instrument to assess attitudes toward lesbians and gay men. Three types of negative attitudes were defined based on a literature review of the various aspects of antigay prejudice. Existing scales were selected and their items were categorized according to expected attitudes. Exploratory factor analysis revealed a scale composed of three negative attitudinal dimensions: two with a more traditional nature (Rejection of proximity and Pathologizing of homosexuality) and a more contemporary one (Modern heterosexism), as well as a positive dimension (Support). All dimensions showed good internal consistency. Additional evidence of the instrument's construct validity was obtained through a differential study, based on the participants' gender and their interpersonal contact with lesbians and gay men.